FORMATION OF ENTREPRENEURIAL COMPETENCIES IN THE HIGHER EDUCATION SYSTEM AS A COMPONENT OF STATE POLICY IN THE FIELD OF PUBLIC ADMINISTRATION IN THE CONTEXT OF ENSURING NATIONAL SECURITY - Androshchuk, Ilona; Horpynchenko, Maksym; Orlova, Anna; Ptashko, Pavlo; Shchelnyk, Oleksandr (Public Management and Policy, 2026)
This article examines the characteristics of the development of entrepreneurial competencies within the higher education system as a component of state policy in the field of public administration in the context of ensuring Ukraine’s national security. The relevance of the study stems from the intensification of globalization challenges, the digitalization of society, the transformation of the labor market, crisis phenomena, and the need to develop adaptive human capital capable of ensuring the country’s economic stability. It has been established that the modern higher education system is transforming from a traditional model of knowledge transfer to an innovation-entrepreneurial model focused on the development of creativity, project-based thinking, digital skills, resilience, and the ability to generate innovative solutions. The study aims to provide a scientific justification for the role of entrepreneurial competencies in the higher education system as a component of state policy in the field of public administration and to develop conceptual approaches to their development in the context of ensuring Ukraine’s national security. The research employed methods of scientific generalization, systematization, comparative analysis, content analysis, logical modeling, systemic and interdisciplinary approaches, as well as methods of analysis, synthesis, induction, and deduction. The analysis of scientific works and European initiatives has revealed the growing importance of entrepreneurial competencies in the modern higher education system and their direct impact on the formation of an innovative knowledge economy. The key stages of the transformation of higher education have been identified: from an elitist model to an innovation- and entrepreneurship-oriented model, accompanied by a shift in the role of higher education institutions within public policy and society at large. It is argued that modern higher education institutions serve not only as institutions for training specialists but also as active creators of innovations, startup ecosystems, technological entrepreneurship, and regional development. An original conceptual model of the interconnection between entrepreneurial competencies, the higher education system, and national security has been developed, according to which the development of entrepreneurial thinking, digital, and managerial competencies creates the prerequisites for the development of startups, the defense-tech sector, the innovation economy, and the enhancement of the state’s competitiveness. It has been determined that the public administration system plays a coordinating and stimulating role in shaping the environment for the development of entrepreneurial competencies through mechanisms of educational, youth, innovation, and regional policy. Practical recommendations are proposed for government agencies and higher education institutions regarding the integration of entrepreneurial competencies into educational programs, the development of startup hubs and business incubators, project-based learning, and the strengthening of cooperation between education, business, and the state. It has been established that the development of entrepreneurial competencies is a vital tool for ensuring economic stability, fostering innovation, and strengthening national security. It has been demonstrated that the modern higher education system should serve as a strategic element of state policy aimed at developing human capital, an innovative environment, and the competitiveness of the national economy. Further research should focus on assessing the economic impact of developing entrepreneurial competencies and their influence on ensuring Ukraine’s national security.